LEGAL RISK MANAGEMENT: STRATEGIES FOR BUILDING BUSINESS SUSTAINABILITY - Loso Judijanto; Iman Hikmat Nugraha; Karman (Prosiding Seminar Nasional Indonesia, 2024)
Legal risk management is the key to success for modern companies to continue their business journey. In a business environment that is increasingly complex and strictly regulated by various legal rules, companies need a proactive approach to identify, assess, and manage their legal risks. This research uses the literature review method as its basis. The results show that effective implementation of legal risk management can help companies comply with legal requirements, avoid unnecessary costs, and maintain a good business reputation. In addition, by integrating legal risk management strategies into the overall business strategy, companies are able to focus more on business innovation and growth. The conclusion is that by proactively managing legal risk, companies can not only prevent potential threats before they become serious problems, but also increase flexibility and adaptability in the face of ever-changing market dynamics. This strategy ultimately establishes a solid foundation for achieving long-term sustainability and growth.